Biopsychosocial risk factors of depression during menopause transition in southeast China - Ketan Chu; Jing Shui; Linjuan Ma; Yizhou Huang; Fan Wu; Fang Wei; Xingjun Meng; Jie Luo; Fei Ruan; Jianhong Zhou (BMC, 2022)
Abstract Objective More than 2 billion women are experiencing menopause transition in China and some of them suffered from depression; while the risk factors of depression during menopause transition were still unclearin China. We aimed to investigate the risk factors in mid-life women in Southeast China. Method This study included 1748 Chinese women aged 40-65 years-old who visited gynecology outpatient department of Women's hospital School of Medicine, Zhejiang University during 2010-2018. Demographic information was collected, and the modified Kupperman Menopausal Index (mKMI) and Hamilton Rating Scale for Depression were assessed. Circulating levels of sex hormones were tested. Ordinal logistic regression analysis was performed to identify risk factors for depression. Results The prevalence of depression symptoms was 47.43%. The majority of women had mild (38.56%) or moderate depressive symptoms (8.00%); only 0.86% had severe depressive symptoms. Compared with perimenopausal women, postmenopausal women had increased risks of more severe depression. The associations between menopausal syndromes and the intensity of depression were strongly positive (OR 6.69, 95% CI 5.39-8.29). Elder age, higher follicle stimulating hormone levels, lower estradiol levels, and fewer parity were positively related with the intensity of depression. Among postmenopausal women, underweight, mKMI > 14, earlier age at menopause, shorter reproductive period, and longer duration after menopause were risk factors for incresed intensity of depression. Conclusions The results demonstrated a high proportion of depression in women complaining of menopause. Menopausal symptoms were strongly related to the intensity of depression. In postmenopausal women, estrogen related events are associated with the intensity of depression. Gynecological endocrinologists in China should consider screening for depression in high-risk women.